Apathy in patients with Alzheimer's disease is a cost-driving factor - Kruse, Christopher; Maier, Franziska; Spottke, Annika; Bach, Jan-Philipp; Bartels, Claudia; Buerger, Katharina; Fellgiebel, Andreas; Fliessbach, Klaus; Frolich, Lutz; Hausner, Lucrezia; Hellmich, Martin; Kloppel, Stefan; et al. (Alzheimers & Dementia, 2023)
BackgroundApathy is the most frequent neuropsychiatric symptom in patients with dementia of the Alzheimer's type (DAT). We analyzed the influence of apathy on the resource use of DAT patients and their caregivers. MethodsIncluded were baseline data of 107 DAT patients from a randomized clinical trial on apathy treatment. The Resource Utilization in Dementia (RUD) instrument assessed costs over a 1-month period prior to baseline. Cost predictors were determined via a least absolute shrinkage and selection operator (LASSO). ResultsOn average, total monthly costs were euro3070, of which euro2711 accounted for caregivers' and euro359 for patients' costs. An increase of one point in the Apathy Evaluation Scale resulted in a 4.1% increase in total costs. DiscussionApathy is a significant cost driving factor for total costs in mild to moderate DAT. Effective treatment of apathy might be associated with reduced overall costs in DAT.
CRIS-Team WoS Importer:2023-01-27